Iron/iron oxide nanoparticles: advances in microbial fabrication, mechanism study, biomedical, and environmental applications. (4th May 2019) - Ashraf, Noreen; Ahmad, Fiaz; Da-Wei, Li; Zhou, Ren-Bin; Feng-Li, He; Yin, Da-Chuan
Abstract: Microbially synthesized iron oxide nanoparticles (FeONPs) hold great potential for biomedical, clinical, and environmental applications owing to their several unique features. Biomineralization, a process that exists in almost every living organism playing a significant role in the fabrication of FeONPs through the involvement of 5–100 nm sized protein compartments such as dodecameric (Dps), ferritin, and encapsulin with their diameters 9, 12, and ∼32 nm, respectively. This contribution provides a detailed overview of the green synthesis of FeONPs by microbes and their applications in biomedical and environmental fields. The first part describes our understanding in the biological fabrication of zero-valent FeONPs with special emphasis on ferroxidase (FO) mediated series of steps involving in the translocation, oxidation, nucleation, and storage of iron in Dps, ferritin, and encapsulin protein nano-compartments. Secondly, this review elaborates the significance of biologically synthesized FeONPs in biomedical science for the detection, treatment, and prevention of various diseases. Thirdly, we tried to provide the recent advances of using FeONPs in the environmental process, e.g. detection, degradation, remediation and treatment of toxic pesticides, dyes, metals, and wastewater.